2022
DOI: 10.1001/jamapsychiatry.2022.1417
|View full text |Cite|
|
Sign up to set email alerts
|

Mismatch Negativity in Response to Auditory Deviance and Risk for Future Psychosis in Youth at Clinical High Risk for Psychosis

Abstract: IMPORTANCEAlthough clinical criteria for identifying youth at risk for psychosis have been validated, they are not sufficiently accurate for predicting outcomes to inform major treatment decisions. The identification of biomarkers may improve outcome prediction among individuals at clinical high risk for psychosis (CHR-P).OBJECTIVE To examine whether mismatch negativity (MMN) event-related potential amplitude, which is deficient in schizophrenia, is reduced in young people with the CHR-P syndrome and associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Presently, the lack of clinical follow-ups in the CHR population impedes determining the progression trajectory of our participants. A longitudinal study is required to establish whether the present effect was driven by those who will transition to SCZ or another chronic psychotic disorder (Fujioka et al, 2020; Hamilton et al, 2022; Perez et al, 2014; Shaikh et al, 2012). However, the observation of significant mMMN reduction in CHR, among whom only few are expected to progress to full-blown psychosis, suggests that MMN might be a potential neurobiological marker in people with a greater risk for psychosis, irrespective of clinical course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Presently, the lack of clinical follow-ups in the CHR population impedes determining the progression trajectory of our participants. A longitudinal study is required to establish whether the present effect was driven by those who will transition to SCZ or another chronic psychotic disorder (Fujioka et al, 2020; Hamilton et al, 2022; Perez et al, 2014; Shaikh et al, 2012). However, the observation of significant mMMN reduction in CHR, among whom only few are expected to progress to full-blown psychosis, suggests that MMN might be a potential neurobiological marker in people with a greater risk for psychosis, irrespective of clinical course.…”
Section: Discussionmentioning
confidence: 99%
“…Sparser findings show that MMN alterations are also present in other populations of patients with psychotic symptoms (Erickson, Ruffle, & Gold, 2016), like in bipolar disorder (BD) (Raggi, Lanza, & Ferri, 2021) and in first-episode psychosis (FEP) (Haigh, Coffman, & Salisbury, 2017), and in subjects at clinical high risk for psychosis (CHR) (Bodatsch, Brockhaus-Dumke, Klosterkotter, & Ruhrmann, 2015;Tada et al, 2019). A recent study with more than 500 CHR participants reported only limited evidence of significant MMN reduction in this population, whereas the MMN deficit was associated with future conversion and earlier onset of full-blown psychosis (Hamilton et al, 2022). Hence, the debate is still open about whether MMN alterations are peculiar to SCZ (Baldeweg & Hirsch, 2015;Erickson et al, 2016;Umbricht et al, 2003) or are instead shared by patients with a history of psychosis.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some clinical studies have indeed measured neural responses to multiple co-occurring auditory feature deviants (e.g., Hay et al, 2015 ) and have found, for example, that MMNs from double deviants combining duration and frequency–but not their constitutive single-deviant MMNs–predict the time to psychosis onset in individuals at high risk for schizophrenia ( Perez et al, 2014 ; Hamilton et al, 2022 ). These studies have, however, not typically assessed MMN(m) additivity per se .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a large mega-analysis of magnetic resonance imaging data in CHR individuals, 61 253 out of 1487 CHR individuals followed up transitioned to psychosis (17%). In a recent multicenter study of MMN among CHR individuals, Hamilton et al 62 reported that 77/315 (24.4%) of followed-up individuals transitioned to psychosis. From the same multicenter study, Seidman et al 63 Although together these findings suggest that combined pitch and duration MMN could be more sensitive to deficits in truly prodromal CHR individuals, 67 as noted by the authors, the effect sizes for each type of MMN are too small to be useful as a risk biomarker.…”
Section: What Kind Of Biomarker Is a Reduction In Mismatch Negativity?mentioning
confidence: 99%